Research on the Mechanism of the Influence of Earthquake-Induced Landslides on the Stress and Deformation Characteristics of Tunnel - Yufang Zhang; Hongyu Liu; Jian Li; Qidi Huang; Xianjie Ma; Wei Li (Advances in Materials Science and Engineering, 2021)
The landslide at the entrance of a railway tunnel in the southwestern region is relatively large, especially due to earthquakes and other factors, which are prone to severe disasters and threaten the safety of the tunnel. Through the long-term monitoring test and numerical calculation analysis on-site, the mechanism of the influence of the earthquake-induced landslide on the characteristics of the tunnel’s force and deformation is studied. The research results show that the earthquake caused the landslide thrust to increase. Because of the existence of the supporting structure, the landslide thrust was consumed, and the remaining part resulted in the compression failure of the tunnel. During the seismic monitoring period, the stress loss of the antislide pile anchor cable was 3.73% and the stress of the second lining of the tunnel increased by 25%. Under the condition of extreme seismic, shear failure occurred at the vault, bottom, and waist of the right-line tunnel, and the tensile strength of the right-line tunnel reached 93.8% of the limit value. For the weak links of the tunnel structure, dense reinforcement planting and strengthening of concrete strength should be adopted to enhance the safety of the tunnel structure. While designing the supporting structure, the rock-socketing depth of the antislide piles and the number of antislide piles should be considered a priority. The impact of the antislide pile spacing is relatively small.